2011
DOI: 10.1186/1471-2334-11-313
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic A/H1N1v influenza 2009 in hospitalized children: a multicenter Belgian survey

Abstract: BackgroundDuring the 2009 influenza A/H1N1v pandemic, children were identified as a specific "at risk" group. We conducted a multicentric study to describe pattern of influenza A/H1N1v infection among hospitalized children in Brussels, Belgium.MethodsFrom July 1, 2009, to January 31, 2010, we collected epidemiological and clinical data of all proven (positive H1N1v PCR) and probable (positive influenza A antigen or culture) pediatric cases of influenza A/H1N1v infections, hospitalized in four tertiary centers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…The percentages of missing data were smaller for the deaths than the survivors (0.4% vs. 36% for time to death/discharge for example), suggesting that data collection was more thorough for patients who died. 210 Poeppl 2011 198 Blumental 2011 202 Yung 2011 195 Altmann 2011 185 Enstone 2011 192 del Rosal 2011 205 Nguyen-Van-Tam 2010 186 Thompson 2011 188 Miranda-Choque 2011 197 Yokota 2011 200 Moretti 2011 208 Yang 2010 191 Mickienė 2011 Results show that when the time-dependent nature of treatment is taken into account appropriately the treatment effects change direction, although none of the results is statistically significant. Adjusting for potential confounders and imputing missing data made little difference to the results.…”
Section: Meta-analysis Of Individual Patient Datamentioning
confidence: 99%
“…The percentages of missing data were smaller for the deaths than the survivors (0.4% vs. 36% for time to death/discharge for example), suggesting that data collection was more thorough for patients who died. 210 Poeppl 2011 198 Blumental 2011 202 Yung 2011 195 Altmann 2011 185 Enstone 2011 192 del Rosal 2011 205 Nguyen-Van-Tam 2010 186 Thompson 2011 188 Miranda-Choque 2011 197 Yokota 2011 200 Moretti 2011 208 Yang 2010 191 Mickienė 2011 Results show that when the time-dependent nature of treatment is taken into account appropriately the treatment effects change direction, although none of the results is statistically significant. Adjusting for potential confounders and imputing missing data made little difference to the results.…”
Section: Meta-analysis Of Individual Patient Datamentioning
confidence: 99%
“…Other studies comparing pandemic influenza with previous seasons have found that children admitted with influenza A(H1N1)pdm09 were older than those admitted with seasonal influenza A in the years prior to the pandemic [3,7,8,26,[30][31][32][33]. Apart from age, no other differences were found in hospitalized and PICU cases during the pandemic period and the 2010/2011 season.…”
Section: Discussionmentioning
confidence: 99%
“…A German observational study reported comorbidities (e.g., chronic respiratory or cardiac disease; neurodevelopmental disorder) in 75% of intensive care unit pediatric admissions due to pandemic influenza (H1N1) [7]. In a Belgian multicenter survey, 47% of children hospitalized with pandemic influenza had similar comorbidities [8].…”
Section: Why Vaccinate High-risk Groups?mentioning
confidence: 98%
“…7 DTaP-IPV administered. 8 DTaP is administered. 9 DTaP is administered (reduced diphtheria and pertussis dose).…”
Section: Children With Chronic Medical Conditionsmentioning
confidence: 99%